An analysis of Masoud Kimiyaei’s novel, Jasadhaye Shishei by - Teymoor Malmir; Sarkoo Nazir Hosein (مطالعات زبانی و بلاغی)
Masoud Kimiyaei is famous for scriptwriting and filmmaking, but he has showcased his art in literary creation by writing a novel, Jasadhaye Shishei. The main question of the present research is to what extent the author is aware of the principles of story writing and has utilized those principles, and to what extent his skill and experience in filmmaking has been effective in writing this novel. In this article, using the method of content analysis, the writing techniques used in the text of the novel and their consistency have been evaluated. The title, chapters and structure of the novel have been explained. The author has been successful in using historiographic metafiction to approach the subject of the story. Characterization of the novel is generally satisfactory; however, in some cases, the narrator passes judgment instead of storytelling through the character’s actions or sayings. The characters language is compatible with their position, level of literacy and responsibility, though the narrator introduces some characters haphazardly. The author utilizes Cinematic capacities thoroughly in giving depth to characterization, narrating details of the setting, activating and visualizing the abstract issues, choosing the viewpoint, mixing discourse with images and depicting poetic exegesis. Meanwhile, the author’s interest in visualization brings about redundant sequencing in the novel, which leads to a voluminous text.